Clinical syndromes of acute and chronic COVID-19 infection among an indigenous high-altitude population during the first and second waves - Melgarejo Pomar, Ingrid Gaby (2023)
Objective: To classify into clinical syndromes the symptoms of acute and chronic COVID-19 infection among a high altitude population during the first and second waves. Materials and methods: A prospective and longitudinal study. An online questionnaire was administered to people infectedwith SARS-CoV-2 during the first and second waves from March 2020 to December 2021. The measures of central tendency were expressed as means and percentages with a 95 % confidence interval. The chi-square test associated the variables and considered a p value ≤ 0.05. IBM SPSS Statistics statistical software V22 was used. Results: A total of 87 women and 63 men with an average age of 44.12 (± 14.56) years participated in the research, out of whom 48.70 % and 51.30 % were infected in the first and second waves, respectively. The 59 reported symptomswere grouped into 19 syndromes for the acute phase and 18 for the chronic phase. The most frequent syndromes in the acute phase were incomplete acute toxic infectious disorders (79.30 %), taste and smell disorders (60.70 %) and anxiety and depressive disorders (56.79 %). Chronic COVID was called post-COVID-19 syndrome and was subdivided into threephases: post-acute, chronic and long-haul. In the post-acute and chronic phases, muscle fatigue and weakness as well as pain and aches appeared, persisting until the long-haul phase, where lingering symptoms were considered sequelae.Post-COVID-19 syndrome occurred in 64.55 % of the participants. Conclusions: This study has shown an increased frequency of symptoms affecting the central and peripheral nervous system in both the acute phase and post-COVID-19 syndrome. It is possible that hypobaric hypoxia, by prolonging inflammation and stimulating oxidative stress, may lead to a longer post-COVID-19 syndrome, with a greater impact on the nervous system.